The implementation of the Regional Development Plan policy focuses on developing the potential of empowered villages in Batu City - Hayat, Hayat; Rudianto, Rudianto; Muchsin, Slamet; Afifuddin, Afifuddin (ARISTO, 2024)
Rural development aims to enhance the well-being and quality of life of rural communities and reduce poverty through the provision of basic needs, infrastructure development, local economic growth, and sustainable utilization of natural resources and the environment. To achieve these goals, the Village Law implements two approaches, namely "Building the Village" and "Village Development," integrated into village development planning. This research employs qualitative descriptive methods to provide a comprehensive and detailed overview of the investigated subject, aiming to understand the implementation of Regional Development Plan Policies focusing on empowering villages in the city of Batu. The study utilizes qualitative descriptive methods and in-depth interviews. The implementation of Regional Development Plan Policies in the city of Batu is documented in the Medium-Term Regional Development Plan (RPJMD) of Batu City for the period 2017-2022 and the Regional Development Plan (RPD) of Batu City for the period 2023-2026. The policy implementation is formalized through Regional Regulations and Local Regulations (Mayor's Regulations) both attributively and delegatively.